Spatial dynamics and urban morphology in a medium-sized brazilian city - Leite, Marcos Esdras (2022)
Contemporary urbanization entails urban transformations of several kinds, especially spatial and economic changes. In the Brazilian urban network, this situation is visibly expressed in medium-sized cities due to their population growth and economic growth that promote regional centralization. Therefore, this article analyzed the expansion of the city of Montes Claro from 1970 to 2020 and the transformations of the urban morphology arising from that process, through geographical data derived from satellite images. The study area was chosen due to the role this city plays in the regional urban area in Northern Minas Gerais. Besides, the attraction of people and capital to that city causes its intra-urban space to undergo an ongoing metamorphosis. As the urban area expands, the formation and consolidation of new centralizations stem from its internal dynamic. As the population density increases and economic activities expand and are relocated, new spaces for consumption and appropriation emerge, engendering new urban habitats and redefining the center and the periphery.